Reinforcing Deficit, Journeying Toward Equity: Cultural Brokering in Family Engagement Initiatives. (August 2016) - Ishimaru, Ann M.; Torres, Kathryn E.; Salvador, Jessica E.; Lott, Joe; Williams, Dawn M. Cameron; Tran, Christine
Families are key actors in efforts to improve student learning and outcomes, but conventional engagement efforts often disregard the cultural and social resources of nondominant families. Individuals who serve as cultural brokers play critical, though complex, roles bridging between schools and families. Using an equitable collaboration lens with boundary-spanning theory, this comparative case study examined how individuals enacted cultural brokering within three organizational contexts. Our findings suggest a predominance of cultural brokering consistent with programmatic goals to socialize nondominant families into school-centric norms and agendas. However, formal leadership and boundary-spanning ambiguity enabled more collective, relational, or reciprocal cultural brokering. These dynamics suggest potential stepping stones and organizational conditions for moving toward more equitable forms of family-school collaboration and systemic transformation.